PERTANGGUNG JAWABAN PIDANA KOORPORASI YANG MEMPRODUKSI KOSMETIK PALSU MEMBAHAYAKAN KESEHATAN KONSUMEN - antoni antoni (Tazir, 2022)
Abstract This research discusses the development of the cosmetic industry which is so rapid that it is able to produce in very large quantities and is supported by advances in science and technology, as well as transportation equipment and marketing systems with digital platforms, which are considered the most strategic during the Covid-19 period. Cosmetics are a daily necessity that is needed by society, especially young women who want to look attractive and beautiful. Even though there have been various provisions governing consumer protection, especially Law Number 8 of 1999 concerning Consumer Protection, fraudulent actors still produce dangerous fake/illegal cosmetics. So the problem raised in this study is how the criminal responsibility of corporations that produce counterfeit cosmetics endangers the health of consumers. Therefore the method used in this study uses normative juridical by studying library materials or library research. From the results of the study it was found that corporations can also be held criminally responsible if they commit a crime. This is due to a paradigm shift in criminal law that corporations are also subjects of criminal law in addition to the existence of natural law subjects, namely, individuals (naturalijk person). So the rejection of corporate punishment based on the university delinquere non potest doctrine has undergone a change by accepting the concept of a functional actor. Keywords: Corporate Criminal Liability, Counterfeit Cosmetics